Place of children with special needs in the education system Early childhood intervention as the odd one out within the services for children with special needs and their families - Czeizel, Barbara; Bakonyi, Anna (Acta Scientiarum Socialium, 2014)
Place of children with special needs in the education system Early childhood intervention as the odd one out within the services for children with special needs and their families The essay intends to demonstrate the problems in the early childhood intervention system, and to provide possible solutions by presenting the outcomes of a pilot model. I will show what phase of this development may be seen in Hungary, what definitions are used within this profession and what causes misunderstandings and misconstructions in the legal regulations. We would like to demonstrate the possible cooperation of the three sectors (medical, educational and social), and what steps have been taken in order to reach the optimal family-centered intervention model.